Attitudes of nursing professionals in light of the cost of care with high-dependency patients - Antônio Fernandes Costa Lima; Valéria Castilho; Juliana Ribeiro Gonçalves (Universidade Federal de Goias, 2014)
The objective was to identify the attitudes of nurses regarding the results of a study on the cost of nursing care with high-dependency patients admitted to a university hospital. Eleven recorded interviews were transcribed, coded, and analyzed by the technique of content analysis and discussed in light of the theoretical framework on cost management. Respondents showed favorable attitudes as to having knowledge of the direct cost of human and material resources and how they contribute to managing the care given to high-dependency patients. They explained that the use of this knowledge will assist in the awareness of professionals, encouraging them to change their attitudes aimed at rational use of the resources available, assessing the real needs of the clientele cared for and avoiding waste. The attitudes of nurses denoted their pre-disposition to appropriate this knowledge concerning the direct cost of resources in order to contribute to managing the care given. doi: 10.5216/ree.v16i4.23473.